Legal Certainty of Crew Protection in Controlled Narcotics Schemes: A Doctrinal Analysis of Mens Rea and Actus Reus - Rudiyanto Rudiyanto; Harmono Harmono (Jurnal Legisci, 2026)
Background. Problems arise when the crew is often positioned as perpetrators of narcotics crimes without adequate evidence related to malicious intent (mens rea) and unlawful acts (actus reus), especially in the context of limited knowledge and control of the ship's cargo. Aims. This article aims to analyze the legal certainty in the protection of crew members who are indirectly involved in controlled delivery schemes, with an emphasis on the doctrinal construction of the elements of mens rea and actus reus in criminal law. Methods. This research employs normative juridical methods, drawing on legislative, conceptual, and comparative legal approaches, and is supported by an analysis of relevant law enforcement practices. Result. The results of the study show that there is a tendency to apply the strict liability approach in narcotics cases involving crew members, which in practice obscures the fundamental principle of geen straf zonder schuld (no crime without fault). In addition, the construction of actus reus is often disproportionately expanded to include individuals who have neither effective control nor real involvement in criminal acts. This condition creates legal uncertainty and may violate the principles of justice and the protection of human rights. Conclusion. This article argues that proof of mens rea should be a central element in the attribution of criminal liability to the crew, and emphasizes the importance of strictly limiting the interpretation of actus reus. As a recommendation, it is necessary to reformulate the narcotics criminal law policy to be more oriented towards the principle of culpability, to strengthen evidentiary standards, and to align it with international legal instruments. Implementation. Thus, it is hoped that a balance will be created between the effectiveness of narcotics eradication and fair legal protection for the crew.